On Composition of Continuity in ideal Topological spaces - Muna Jabbar Mohammad; Faik Mayah (Wasit Journal for Pure Sciences, 2022)
We define new classes of sets called pre- ̂-closed set and pre- ̂-open set. Also we define new ideal topological spaces is called ̂-spaces, the notion of pre- ̂-closed set in is applied to study a new class of functions, continuous function and composition of continuity in ideal topological spaces, so that we investigate some properties, characterizations of these functions.